Is there an association between ultra-processed food consumption and ovarian cancer risk in women? : A Systematic Review - Amanda Ezra Natasya Napitupulu; Jenary Immanuel Surbakti (International Medical Journal Corp. Ltd, 2026)
Introduction: Ultra-processed foods (UPF) have been implicated in chronic disease development, but their association with ovarian cancer—a leading cause of gynecologic cancer mortality—requires systematic evaluation. This review examines evidence linking UPF consumption to ovarian cancer risk. Methods: We systematically reviewed observational studies assessing UPF consumption (using NOVA classification or quantitative methods) and ovarian cancer incidence or mortality in adult women. Nine studies met inclusion criteria. Results: The UK Biobank prospective cohort (197,426 participants; 143 ovarian cancer cases; 9.8 years follow-up) demonstrated significant positive associations between UPF consumption and ovarian cancer incidence (HR 1.19 per 10% increment; 95% CI: 1.08–1.30; p<0.001) and mortality (HR 1.30; 95% CI: 1.13–1.50). Supporting evidence from case-control studies showed preserved foods consumption (>13.5 g/day) was associated with 78% increased odds of epithelial ovarian cancer (OR 1.78; 95% CI: 1.35–2.34), while a